Pengaruh motivasi kerja dan kepemimpinan terhadap kepuasan kerja karyawan pada Karoseri Akai Pekanbaru - Anggi Teguh; Machasin '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at the Company's Autobody Akai Pekanbaru. This study aims to determine how Effect of Work Motivation and Leadership either simultaneously or partially on Employee Satisfaction Autobody Akai Pekanbaru.The population in this study were all full-time employees that exist in Pekanbaru Akai Autobody totaling 42 people, with a total sample of 42 employees. The method of analysis used in this study is the method Multiple Regression Analysis using SPSS version 17.00.Simultaneous regression test (F test) showed that the independent variables studied (Work Motivation and Leadership) simultaneously have a significant effect on the dependent variable (Employee Satisfaction). The magnitude of the effect that (R2) by the two independent variables together against the dependent variable 41.70%, while the remaining 58.30% is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Work Motivation and Leadership) has a significant effect on the dependentvariable (Employee Satisfaction).Keywords: Work Motivation, Leadership and Job Satisfaction